2011
DOI: 10.1016/j.ajpath.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 Selectively Enhances the Neuroprotective Effects of Microglia to Attenuate Oligomeric Amyloid-β Neurotoxicity

Abstract: Microglia, macrophage-like resident immune cells in the brain, possess both neurotoxic and neuroprotective properties and have a critical role in the development of Alzheimer's disease (AD). We examined the function of Interleukin-34 (IL-34), a newly discovered cytokine, on microglia because it reportedly induces proliferation of monocytes and macrophages. We observed that the neuronal cells primarily produce IL-34 and that microglia express its receptor, colony-stimulating factor 1 receptor. IL-34 promoted mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 35 publications
(29 reference statements)
7
131
0
1
Order By: Relevance
“…IL-34 reporter expression revealed that within the brain, IL-34 is highly expressed predominantly in the cortex, the anterior olfactory nucleus, and the hippocampus (Figure 3A), whereas no or very low expression could be detected in the brain stem and cerebellum (data not shown). IL-34 was specifically expressed by neurons (Figure 3B) as previously suggested (Mizuno et al, 2011). In adult Il34 LacZ/LacZ mice, microglia were partially reduced, most pronounced in areas correlating with high IL-34 expression (Figures 3C–3E).…”
Section: Resultssupporting
confidence: 83%
“…IL-34 reporter expression revealed that within the brain, IL-34 is highly expressed predominantly in the cortex, the anterior olfactory nucleus, and the hippocampus (Figure 3A), whereas no or very low expression could be detected in the brain stem and cerebellum (data not shown). IL-34 was specifically expressed by neurons (Figure 3B) as previously suggested (Mizuno et al, 2011). In adult Il34 LacZ/LacZ mice, microglia were partially reduced, most pronounced in areas correlating with high IL-34 expression (Figures 3C–3E).…”
Section: Resultssupporting
confidence: 83%
“…Accordingly, the pharmacological inhibition of CSF-1R decreases microglia reactivity and extends the life span of ALS mice [10,19]. Astrocytes are another major source of M-CSF and IL-34, both factors being potent agonists of the CSF-1R [20,21]. In support of this hypothesis, previous studies have shown that the intraperitoneal administration of M-CSF to ALS mice induced microglia proliferation, also exacerbating disease progression [22].…”
Section: Discussionsupporting
confidence: 62%
“…3d). Recent studies have shown that IL-34 is primarily produced by neurons, specifically directs the differentiation of myeloid cells in the developing CNS and determines the phenotype discrepancy in M-CSF-deficient and M-CSFR-deficient mice described above (Mizuno et al, 2011; Nandi et al, 2012; Wang et al, 2012). IL-34 deficiency mainly affects development but not the ability of microglia to produce inflammatory cytokines (Greter et al, 2012; Nakamichi et al, 2013; Wang and Colonna, 2014).…”
Section: Discussionmentioning
confidence: 99%